Possible Effects of Bright Light Therapy on Electroencephalogram-Vigilance in the Treatment of Depression in Adolescents: A Pilot Study - Berger, Christoph; Dück, Alexander; Gest, Stephanie; Jonas, Lena; Kölch, Michael; Martin, Franziska; Reis, Olaf; Schroth, Jennifer; Legenbauer, Tanja; Holtmann, Martin (Frontiers in Psychiatry, 2022)
Background: Chronotherapeutic treatments for depression, such as bright light therapy (BLT), are non-invasive and produce almost no side effects. However, study evidence for reliable neuro-biological changes associated with treatment response is still rare. Several studies using EEG-vigilance indicate a higher arousal and a later decline during resting state in adult de-pressive patients compared to healthy controls. To our knowledge there are no study re-ports on EEG-vigilance in depressive youth to date. Methods: 11 adolescents with depression receiving BLT were compared to 11 age and gender-matched patients with depression receiving treatment as usual. The BLT was administered in the morning within two weeks on five consecutive days per week. The depressive symp-tomatology was assessed using the Beck Depression Inventory (BDI-II) and the resting state electroencephalogram (EEG) of 20 minutes was recorded. EEG and BDI-II were as-sessed bevor and after 10 days of treatment. Vigilance level and vigilance decline was es-timated using the VIGALL toolbox. Results: Brain arousal increased after 10 days of bright light therapy in adolescents with depres-sion. Severe depressive symptoms were associated with higher brain arousal level; BDI-II sum score correlated negatively with amount of drowsiness Limitations: The sample size was small and participant’s brain arousal at baseline was not matched and differed between BLT and TAU groups. Conclusions: BLT might have an additional effect on the brain arousal. EEG-vigilance seems to be a reli-able and valid marker for neurobiological changes probably associated with depression and its treatment and therefore might be of clinical relevance.